The Effectiveness of Indonesia’s Feed-in-Tariff Implementation to Improve Business Interest in Renewable Energy Case: The Simulation for Solar Farm in Weh Island (Aceh-Indonesia) - Rahmawati, Sri; Salam, Rudi (Institut Teknologi Sepuluh Nopember, 2020)
The support of the Indonesian government in encouraging the achievement of renewable energy targets is to impose a Feed in Tariff (FiT) rule as a benchmark purchase price through the State Electricity Provider (PLN). The Ministry of Energy and Mineral Resources in 2013 determined that, the FiT for the Aceh region was 17 cents, where the highest FiT in Indonesia could reach 30 cents. In 2017 a new regulation was issued, in which FiT was set at 85% of regional production costs (BPP). In fact, currently BPP available on Weh Island reach more than Rp. 2,500 / kWh, with an average selling price to the community of Rp. 900, - / kWh. This BPP is more expensive than the price setting by the Government in 2017 of Rp 1,733 / kWh. In measuring the FiT's effectiveness, the evaluation solved based on economic valuation. Simulations were carried out for the capacity of 1 and 5 MW solar farms using 2 different panel components by comparing the prices of FiT BPP determined by the government and BPP in actual conditions. The results showed that, simulations with a capacity of 1 MW, using 85% of the government's BPP, were ineffective and not feasible based on economic calculations. whereas with FiT based on actual BPP, the profit to be achieved is about 42-45% / kwh with return-on-investment capital in the 10th year. The simulation with 5 MW capacity shows an effective and feasible profit if it use the actual BPP condition of the FiT with an effective profit value around 49-56% / kwh.